Case report: Prostatic malakoplakia: a rare disease that has a profile mimicking prostate cancer - Ren, Yelei; Chen, Weihao; Zhang, Mengni; Zhang, Xuhui; Zhou, Jiaojiao; Li, Yongzhong; Cai, Diming (Frontiers in Oncology, 2024)
Prostatic malakoplakia (PMP) is a rare inflammatory disease. Imaging misdiagnosis is a major reason for unnecessary punctures but the information is even less. Five patients with PMP between May 2022 and February 2023 were enrolled in this study to summarize its imaging manifestations. All patients underwent prostate biopsy with ultrasound (US) guided and confirmed by pathology, and the presence of prostate cancer was also excluded by pathology. Five patients with a median age of 71 years ( range:58-74 years) and a median total prostate-specific antigen (T-PSA) of 10.40ng/ml (range: 1.74-63.42ng/ml). Chest computed tomography of two patients showed pulmonary infections. All patients underwent magnetic resonance imaging (MRI), four of them had a prostate imaging reporting and data system (PIRADS) score of 5, and one had a score of 4, the lesions are mostly distributed in the peripheral zone of the prostate and appeared as high signal on T1-weighted imaging (T1WI) and low signal on T2-weighted imaging (T2WI). In the US examination, four patients had abnormal prostate morphology with an unsmooth envelope and nonuniform parenchymal echogenicity. Four patients had increased prostate volume. US showed a hypoechoic nodule with non-uniform internal echogenicity, abundant internal blood flow signal was detected by color Doppler US. PSA, MRI, and US were not specific for PMP in our study, but we found that a history of co-infection may be helpful in the accurate diagnosis diagnosis of the disease and avoid unnecessary biopsy.